2023
DOI: 10.1186/s40337-022-00731-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and management of disorders of gut–brain interaction in patients with eating disorders

Abstract: Disorders of gut–brain interaction (DBGI), also known as functional gastrointestinal disorders, are common in individuals with eating disorders, and may precede or perpetuate disordered eating. Understanding the pathophysiology of common gastrointestinal symptoms in DGBI can be important for the care of many patients with eating disorders. In this review, we summarize the literature to date on the complex relationship between DBGI and eating disorders and provide guidance on the assessment and management of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 83 publications
(131 reference statements)
1
11
0
Order By: Relevance
“…Up to 40% of DGBI patients meet criteria for symptoms of ARFID, 9 particularly those with a history of restrictive diets 10 . While ARFID‐like symptoms are common among DGBI patients, we found only eight papers that meet keywords for both ARFID and DGBI on PubMed to date 9,11–17 . In addition, since ARFID has been first described by the DSM‐5 in 2013, the current literature on this eating disorder among adult population is very limited.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Up to 40% of DGBI patients meet criteria for symptoms of ARFID, 9 particularly those with a history of restrictive diets 10 . While ARFID‐like symptoms are common among DGBI patients, we found only eight papers that meet keywords for both ARFID and DGBI on PubMed to date 9,11–17 . In addition, since ARFID has been first described by the DSM‐5 in 2013, the current literature on this eating disorder among adult population is very limited.…”
Section: Discussionmentioning
confidence: 94%
“…10 While ARFID-like symptoms are common among DGBI patients, we found only eight papers that meet keywords for both ARFID and DGBI on PubMed to date. 9,[11][12][13][14][15][16][17] In addition, since ARFID has been first described by the DSM-5 in 2013, the current literature on this eating disorder among adult population is very limited. Studies are heterogeneous with regard to their methodology.…”
mentioning
confidence: 99%
“…Recognizing and managing DGBI symptoms in patients with AN is a crucial aspect of clinical practice; untreated DGBIs can distract from the primary pathology of an ED, perpetuate disordered eating behaviors and hinder nutritional rehabilitation. A comprehensive evaluation to rule out structural or organic causes is essential, and management may involve reassurance, neuromodulators and complementary therapies [ 15 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Santonicola et al [ 5 ] reported a high incidence of functional dyspepsia (FD) and postprandial distress syndrome (PDS) in AN patients. Recent studies using Rome IV criteria have corroborated these findings, emphasizing the importance of assessing and managing DGBIs in ED patients, including those with restrictive food intake disorders [ 8 , 15 ].…”
Section: Introductionmentioning
confidence: 93%
“…Disorders of gut-brain interaction, previously referred to as “functional” gastrointestinal disorders, including irritable bowel syndrome, are increasingly recognized as common maladies of people with eating disorders. Thus, we are pleased to include a thorough review of DGBI and their management in the context of eating disorders [ 7 ]. Furthermore, a review of the microbiome and its potential burgeoning implications in people with eating disorders is presented [ 8 ].…”
Section: Main Textmentioning
confidence: 99%